Pomegranate Juice Diminishes The Mitochondria-Dependent Cell Death And NF-kB Signaling Pathway Induced By Copper Oxide Nanoparticles On Liver And Kidneys Of Rats - Hassanen EI (Dove Medical Press, 2019)
Eman I Hassanen,1,* AF Tohamy,2,* Marwa Y Issa,3,* Marwa A Ibrahim,4,* Khaled Y Farroh,5,* Azza M Hassan1,* 1Pathology Department, Faculty of Veterinary Medicine, Cairo University, Giza, Egypt; 2Toxicology and Forensic Medicine Department, Faculty of Veterinary Medicine, Cairo University, Giza, Egypt; 3Pharmacognosy Department, Faculty of Pharmacy, Cairo University, Giza, Egypt; 4Biochemistry Department, Faculty of Veterinary Medicine, Cairo University, Giza, Egypt; 5Nanotechnology Department, Agricultural Research Center, Giza, Egypt*These authors contributed equally to this workCorrespondence: Marwa A IbrahimBiochemistry, Faculty of Veterinary Medicine, Cairo University Email marwaibrahim@cu.edu.egBackground: Pomegranate (Punica granatum L) has been used since ancient times in the traditional medicine of several cultures, particularly in the Middle East. It is an essential commercial crop full of bioactive compounds with several medical applications. Pomegranate is very popular for its biological effects exerted by phenolic compounds via free radical scavenging abilities. It has revealed high antioxidant and anti-inflammatory activities and is beneficial for the amelioration of liver and kidney diseases.Purpose: To elucidate the potential efficacy of pomegranate juice (PJ) against copper oxide nanoparticles (CuO-NPs)-induced apoptosis, inflammation, and oxidative stress damage.Study design: 37 nm sized CuO-NPs were prepared by precipitation method and characterized by using X-ray diffractometer (XRD), Zetasizer nano-and high-resolution transmission electron microscope (HR-TEM). 30 Wistar rats were partitioned into 6 equal groups as follows: Group 1 (negative control), groups 2 & 3 (PJ control groups), group 4 (CuO-NPs group), groups 5 & 6 (CuO-NPs + PJ groups). Methods: Hepato-renal protective effect of PJ was evaluated by measuring levels of serum marker enzymes (ALT, AST,blood urea nitrogen and creatinine). Cu NPs bioaccumulation in liver and kidneys was determined by using atomic absorption spectrophotometer. The oxidative stress markers, Rt-PCR analysis, histopathological and immunohistochemical studies were carried out in the liver and kidneys to support the above parameters.Results: Rats injected with CuO-NPs showed higher levels of the above serum marker enzymes, alteration of oxidant–antioxidant balance together with severe pathological alterations in liver and kidney tissues and overexpression of both caspase-3 and nuclear factor kappa B protein (NF-ĸB) associated with upregulation of Bax gene and downregulation of Bcl2 gene in these organs. PJ ameliorated all of the above toxicological parameters.Conclusion: PJ was proved to be a potential hepato-renal protective agent against liver and kidney damage induced by CuO-NPs via its antioxidant, anti-inflammatory, and anti-apoptotic effects.Keywords: apoptosis, nanoparticles, pomegranate, histopathology, gene